Temperature Incubation During the Embryo-Larval Stage for Inducing Sex Reversal of Nile Tilapia Red NIFI Strain - Soleh, Mohamad; Aulia, Rahma; Naryaningsih, Agustien; Ruliaty, Lisa; Nur, Abidin (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to achieve male sex reversal in Nile Tilapia (Orechromis niloticus) of the red NIFI strain through high-temperature incubation during the embryonic or pre-swimming larval phase. Larvae resulting from the natural mating of red NIFI strain broodstock were incubated under temperature treatments of 31oC, 33oC, 35oC, and a control group (<30oC), each with three replicates. Temperature regulation was facilitated using a heater.Â During the initial 3 hours of incubation, the heater was turned off for 6 hours, followed by another 3 hours of incubation with the heater on. This pattern was repeated daily until the larvae began to swim. The treated larvae were then reared for 90 days. Thirty specimens from each replicate were identified for gender using the squash acetocarmine method. The study results indicated that temperature differences significantly influenced (p<0.05) the sex ratio of Nile tilapia in the red NIFI strain. The highest proportion of males was achieved at 33oC, at 73.33%, and 35oC, at 64.43%. There were no significant differences (p>0.05) in fry survival rates at 7 days and after 90 days of rearing.